Comparison of in-plane compression of additively manufactured Ti6Al4V 2D auxetic structures: Lattice design, manufacturing speed, and failure mode - Eren, Zana; Gokcekaya, Ozkan; Balkan, Demet; Nakano, Takayoshi; Mecitoğlu, Zahit (Elsevier BV, 2024)
The metal-based 2D auxetic lattice structures hold the potential for multifunctional tasks in aerospace applications. However, the compression response of those manufactured by powder bed fusion process is underexplored. This study proposes a comprehensive comparison of in-plane quasi-static compression performance of 2D auxetic lattice structures, utilizing three designs (anti-tetrachiral (ATC), double arrow-headed (DAH), and tree-like re-entrant (TLR)), manufactured with stiff Ti6Al4V by the electron beam powder bed fusion process (PBF-EB) with various manufacturing speeds. The results revealed unique failure patterns and superior energy absorptions among 2D lattice structures in the literature. TLR design enhanced energy absorption by overcoming failures between DAH columns and exhibited the lowest standard deviations in specific energy absorption (SEA) values (9.75 %–12.62 %). Besides, Kernel average misorientation (KAM) values followed the order of DAH, TLR, and ATC, and inversely correlated with SEA values. ATC structures with the lowest KAM outperformed DAH and TLR by 47.5 % and 6.44 %, respectively. Scan speed variations affected SEA and porosity values differently for each lattice design while exhibiting similar microstructure characteristics. The findings in this study propose a significant contribution to the development of aerospace sandwich structures where harsh environments exist and employment of 2D topologies are required.
Keywords: Additive manufacturing; Energy absorption; Residual stress; TA401-492; Auxetic structures; Compressive failures; Materials of engineering and construction. Mechanics of materials